Governing ourselves? : the politics of Canadian communities - McAllister, Mary Louise, 1957- (UBC Press, 2004)
"This book covers traditional topics such as government structures and institutions and intergovernmental relations. It also reaches more broadly into areas of inquiry relevant to geography, urban planning, environmental studies, public administration, sociology, and Canadian studies."--Jacket.